5G Enabled Secure Wireless Networks - Jayakody, Dushantha Nalin K.; Srinivasan, Kathiravan; Sharma, Vishal; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book covers issues related to 5G network security. The authors start by providing details on network architecture and key requirements. They then outline the issues concerning security policies and various solutions that can handle these policies. Use of SDN-NFV technologies for security enhancement is also covered. The book includes intelligent solutions by utilizing the features of artificial intelligence and machine learning to improve the performance of the 5G security protocols and models. Optimization of security models is covered as a separate section with a detailed information on the security of 5G-based edge, fog, and osmotic computing. This book provides detailed guidance and reference material for academicians, professionals, and researchers. Presents extensive information and data on research and challenges in 5G networks; Covers basic architectures, models, security frameworks, and software-defined solutions for security issues in 5G networks; Provides solutions that can help in the growth of new startups as well as research directions concerning the future of 5G networks.
Chapter1: 5G Enabled Wireless Networks: A Security, Data and Privacy Perspective -- Chapter2: 5G Applications and Architectures -- Chapter3:A Survey on the Security and the Evolution of Osmotic and Catalytic Computing for 5G Networks -- Chapter4: Physical Layer Security in 5G Hybrid Heterogeneous Networks -- Chapter5: Physical Layer Security of Energy Harvesting M2M Communication System -- Chapter6: Beam-Domain Full-Duplex Massive MIMO Transmission in the Cellular System.
Keywords: Telecommunication; Electric power production; Data protection; Electronics; Application software; Energy policy; Energy and state; Communications Engineering, Networks; Electrical Power Engineering; Data and Information Security; Electronics and Microelectronics, Instrumentation; Computer and Information Systems Applications; Energy Policy, Economics and Management